STUDI TRANSPORT PESTISIDA ENDOSULFAN DALAM TANAH SKALA LABORATORIUM - Alfiah , Taty
Understanding of pesticide transport in soil is essential in order to predict pesticide movement and the potential of groundwater contamination. One dimentional transport equation can quantitatively describe pesticide movement with infiltrating water and its interactions with soil components. Laboratory experiments, batch adsorpstion and disturb soil columns were performed with endosulfan, as Akodan 35 EC [350 gr/ml]. The endosulfan solutions used in the batch adsorption had initial concentration between 175-525 mg/1 and 175 mg/t for soil columns. All the experiments were conducted with silt loam and clay soils that were collected from agricultural area, Lembang and Ciburial, Bandung. The adsorption isoterrn of endosulfan were presented using Freundlich equation to described instantaneous adsorption and Barrow-Shaw equation to destribed time dependent adsorption. Freundlich equation for Lembang and Ciburial soil were : S = 1,03. C1\'29 and S = 1,4 . C1\'24, while Barrow-Shaw equation were S = 1,31 . C1\'29 t0,45 and S = 1,62 . Cl\'25 . t0,34 for Lembang soil and Ciburial soil. Dispersion coefficient [D] were estimated by fitting on an analitical solution to Cl- column experiments breakthrough curve. D of Lembang soil was 37,5 cm2/day with SSE = 0,15 and 195 cm2/day for Ciburial soil with SSE = 0,09. [SSE=sum square of error]. Endosulfan transport coefficient were predicted by fitting on numerical solution to endosulfan columns experiments breakthrough curve. Advective transport, hydrodinamic dispersion, and time dependent adsorption were accounted in the numerical solution. Coefficient resulted from the batch adsorption using Barrow-Shaw equation were used as first estimated of endosulfan transport coefficient. Transport coefficients of endosulfan in Lembang soil were k=11, m~,35 retardation [R]=17, SSE = 0,16 , and k-45, n=0,95, m=0,25, retardation [R]=28 with SSE~,14 in Ciburial soil. [SSE=sum square of error]. This study demonstrated that Ciburial soil had greater capacity than Lembang soil to retain endosulfan during transport through soil.